An Analysis of Feminism in Gunpowder Milkshake Movie - Gofur, Abdul Gofur; priyoto, priyoto (STIBA IEC JAKARTA, 2025)
In patriarchal societies, traditional stereotypes often restrict women's roles, portraying them as weak, emotional, and dependent on men. These stereotypes affect daily life and media representations, including film. This study analyzes how feminist values related to gender discrimination are represented in the action film Gunpowder Milkshake. The film was selected for its unique perspective on gender dynamics in a male-dominated genre. Using a qualitative descriptive approach, the research focuses on five forms of gender discrimination: marginalization, subordination, stereotyping, violence, and burden. The analysis shows that Gunpowder Milkshake features strong and independent female characters who challenge traditional stereotypes and fight against oppression. The film portrays the struggles of women to gain recognition in a male-dominated world (marginalization), the control and imposed roles they face (subordination), and how they defy gender stereotypes. It also uses violence to highlight power dynamics and explores the emotional burdens faced by the protagonist, Sam. In conclusion, the findings of this research as identified and analyzed various gender themes present in the film Gunpowder Milkshake, particularly those related to marginalization, subordination, stereotyping, violence, and the burdens faced by female characters.